Respuesta :
The required system that can be obtained by substituting is
2 (1 - 2c) + 3c = 5, because a = 1 - 2c.
Given the system of equation;
2a + 3c = 5
a +2c=1
This system can be solved using the substitution method.
From equation 2:
- a = 1 - 2c ...................... 3
Substitute equation 3 into 1 will give:
- 2a + 3c = 5
- 2 (1- 2c) + 3c = 5
Hence the required system that can be obtained by substituting is
2 (1 - 2c) + 3c = 5, because a = 1 - 2c.
Learn more on simultaneous equation here: https://brainly.com/question/16863577